Efektivitas Media Zep Quiz dalam Meningkatkan Minat Belajar PAI di SMP Negeri 1 Ketanggungan - Hayatun Husna Amalia; Harisatunnisa Harisatunnisa (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study evaluates the effectiveness of using Zep Quiz media in boosting student learning interest at SMP Negeri 1 Ketanggungan. The author based this research on the low enthusiasm for learning in Islamic Religious Education (PAI) and Character Building subjects due to the implementation of conventional methods that lack interaction. To address this problem, this research applied a quantitative approach through a quasi-experimental method with a Nonequivalent Control Group design involving an experimental class and a control class. The researchers collected research data comprehensively through a learning interest questionnaire, direct observation, and documentation techniques. Next, the research team processed all the data obtained using statistical analyses, including normality tests, hypothesis tests, and N-Gain calculations. The final data showed a significant surge in interest in learning in the experimental class. The high post-test scores and N-Gain values ​​​​prove that the Zep Quiz platform successfully creates an interactive and enjoyable classroom atmosphere. This research concludes that the use of Zep Quiz is very effective in igniting learning enthusiasm and is an innovative digital media option.   Keywords: Zep Quiz, Interest In Learning, Islamic Education, Learning Media